Methods for the detection and characterization of boat paint microplastics in the marine environment - Gondikas, Andreas; Mattsson, Karin; Hassellöv, Martin (Frontiers in Environmental Chemistry, 2023)
Microplastics in the marine environment have been the focus of intense research recently, however little attention has been given to boat paint sources, despite its direct influence on the marine ecosystem. This is largely due to the lack of established analytical methods. Microplastics from boating sources may originate from antifouling paints on the underwater body, surface coatings on the top sides, deck, and superstructure, as well as plastic parts of the boat construction. Their release can occur during construction, operation (leisure boats and commercial ships), service, and maintenance, from the materials themselves or used chemicals (e.g., abrasive detergents). Most importantly, boat paint microplastics containing biocides, such as the metals copper and zinc, and particles containing tin (residues from old or current use of tributyl-tin ship hull paints) should raise higher concern on potential environmental impacts. This study aims to provide practical insight on methods for the quantification of boat paint microplastics in marine waters and provide a baseline survey on their occurrence. Sampling and analysis methods are applied on case studies, i.e., marinas on the Swedish coast. A multi-method approach for identifying and characterizing boat paint microplastics based on visual and chemical characteristics is presented. In general, the measured content of biocide-containing microplastics was remarkably high in all marinas, with concentration levels of copper-rich particles >10 μm between 400 and 1400 particles per L. Given that biocide paint particles are manufactured to be toxic, it is particularly important to take into account field measurements in future environmental status assessments. This work underlines the importance of monitoring data in the action work between relevant authorities and stakeholders.